NMR-based metabolomics for quality control of Dukung Anak (Phyllanthus niruri Linn.) and identification of biomarkers for its diabetes-related activities - Mediani, Ahmed (2016)
Phyllanthus is a plant genus that has been used in traditional medicine due to its phytomedicinal metabolites content. However, there is a lack of consistency and efficacy of plant of this genus as well as not enough scientific reports to support its traditional uses specifically in treating diabetes. The main aim of this study was to investigate the antidiabetic properties of Phyllanthus in vitro and in vivo using metabolomics approach. The first part of the present study determined the variation between two Phyllanthus species (P. niruri and P. urinaria) at different growth stages (8, 10 and 12 weeks) using proton nuclear magnetic resonance (1H NMR) combined with multivariate data analysis (MVDA). The results revealed that the Principal Component Analysis (PCA) and Partial Least Square (PLS) showed ideal differentiation between these species, suggesting the contributed metabolites, which were responsible for the discrimination. Phyllanthus niruri extracted with 80% ethanol possessed high antioxidant and α-glucosidase inhibitory activities compared to P. urinaria and 10 weeks was the valuable growth age that provides P. niruri extract with the highest content or/and number of bioactive metabolites. Thus, P. niruri harvested at 10 weeks was selected in the second part of the study to optimize the appropriate drying method and solvent for extracting these bioactive components. Three extracting solvents (methanol, ethanol and water) with different ratios were assessed for their effects on biological activities of P. niruri subjected to three drying treatments (air, oven and freeze). The freeze-dried P. niruri samples that were extracted with 80% ethanol exhibited higher biological activity values compared to the other extracts. The 80% ethanol extract had the quantities of epicatechin (172.0 μg/g), ellagic acid (46.67 μg/g), chlorogenic acid (44.33 μg/g), quercetin (1.73 μg/g), catechin (1.63 μg/g), phyllanthin (46.0 μg/g), and hypophyllanthin (23.17 μg/g) analyze using high performance liquid chromatography (HPLC). In the third part of this study, the correlation was also determined among the phytochemical constituents and the bioactivities using PLS regression. The identified phenolics and hypophyllanthin were strongly correlated with the antioxidant and α-glucosidase inhibitory activities, suggesting their great contributions to these activities. The optimized P. niruri extract was further evaluated for in vivo antidiabetic properties at two concentrations (250 and 500 mg/kg body weight) and compared with metformin. The effect of P. niruri extract on the biochemical parameters of obese–diabetic rats was also investigated. The development of the obese diabetic model was done by feeding the high fat diet to Sprague-Dawley rats and inducing diabetic condition with a low dose of streptozotocin (STZ). The in vivo results indicated that P. niruri extracts of 500 mg/kg bw displayed the management of metabolites disorders of obese diabetic rats toward the normal state. The phytochemicals of P. niruri extracts might improve the metabolic disorders caused by diabetes. The extract at a concentration of 500 mg/kg bw also exhibited a noticeable effect in declining the plasma glucose level and improving lipid profile in obese diabetic rats as compared to 250 mg extract/kg bw. Both P. niruri doses showed reduction in the plasma cholesterol and low-density lipoprotein (LDL) levels and an increase in high-density lipoprotein (HDL). The effect of various metabolites in controlling the diabetes syndromes was discussed. The present study suggested that P. niruri can be a prominent and constructive medicinal plant. In conclusion, 1H NMR-based metabolomics approach was successfully used to optimize the postharvest parameters, provide insights into the efficacy of P. niruri as a remedy for diabetes, and set the preliminary step towards developing this herb into high claim products.